Intrapartum‐related perinatal deaths in births planned in midwifery‐led settings in Great Britain: findings and recommendations from the ESMiE confidential enquiry. (10th June 2020) - Rowe, R; Draper, ES; Kenyon, S; Bevan, C; Dickens, J; Forrester, M; Scanlan, R; Tuffnell, D; Kurinczuk, JJ
Abstract : Objective: To review quality of care in births planned in midwifery‐led settings, resulting in an intrapartum‐related perinatal death. Design: Confidential enquiry. Setting: England, Scotland and Wales. Sample: Intrapartum stillbirths and intrapartum‐related neonatal deaths in births planned in alongside midwifery units, freestanding midwifery units or at home, sampled from national perinatal surveillance data for 2015/16 (alongside midwifery units) and 2013–16 (freestanding midwifery units and home births). Methods: Multidisciplinary panels reviewed medical notes for each death, assessing and grading quality of care by consensus, with reference to national standards and guidance. Data were analysed using thematic analysis and descriptive statistics. Results: Sixty‐four deaths were reviewed, 30 stillbirths and 34 neonatal deaths. At the start of labour care, 23 women were planning birth in an alongside midwifery unit, 26 in a freestanding midwifery unit and 15 at home. In 75% of deaths, improvements in care were identified that may have made a difference to the outcome for the baby. Improvements in care were identified that may have made a difference to the mother's physical and psychological health and wellbeing in 75% of deaths. Issues with care were identified around risk assessment and decisions about planning place of birth, intermittent auscultation, transfer during labour, resuscitation and neonatal transfer, follow up and local review. Conclusions: These confidential enquiry findings do not address the overall safety of midwifery‐led settings for healthy women with straightforward pregnancies, but suggest areas where the safety of care can be improved. Maternity services should review their care with respect to our recommendations. Tweetable abstract: Confidential enquiry of intrapartum‐related baby deaths highlights areas where care in midwifery‐led settings can be made even safer. Tweetable abstract: Confidential enquiry of intrapartum‐related baby deaths highlights areas where care in midwifery‐led settings can be made even safer.